Association of cumulative exposure to Chinese visceral adiposity index and gastrointestinal cancer: a prospective cohort study - Li, Jiaxing; Ma, Chao; Liu, Kuan; Wang, Wanchao; Cui, Shuqing; Tian, Yuan; Dong, Zhigang; Wei, Wenqiang; Wu, Shouling; Liu, Siqing (Frontiers in Oncology, 2025)
BackgroundUsing the Kailuan Cohort, we investigated the association between cumulative exposure to the Chinese visceral adiposity index (CVAI) and the risk of developing gastrointestinal (GI) cancers.MethodsA prospective cohort study was conducted among participants who underwent three consecutive health examinations in the Kailuan Cohort from 2006 to 2010. Participants were categorized into quartiles based on their cumulative CVAI (cumCVAI). The cumulative incidence of GI cancers was estimated using Kaplan-Meier curves. The dose-response relationship between CVAI and the risk of developing GI cancers was examined using restricted cubic spline (RCS) in multivariable adjusted models. Multivariate Cox proportional hazards regression analysis was performed to assess the association between cumCVAI quartiles and the incidence of GI cancers. Furthermore, subgroup analyses and sensitivity analyses were conducted.ResultsA total of 44,213 individuals were included in this study. The incidence rates of GI cancers per 1,000 person-years for the Q1 to Q4 groups were 1.00,1.45,1.62 and 2.11, respectively. The RCS curve demonstrated a significant dose-response relationship between cumCVAI and the occurrence of GI cancers events (P for overall trend < 0.001; P for nonlinear trend < 0.001). After adjusting for potential confounders, compared with the Q1 group, the risk of GI cancers was significantly elevated in the Q2 group (HR 1.26; 95% CI 1.01, 1.58), Q3 group (HR 1.31; 95% CI 1.05, 1.64), and Q4 group (HR 1.48; 95% CI 1.19, 1.85). This association was particularly evident in older individuals, females, those with a BMI ≥ 24 kg/m2, non-smokers, and non-drinkers.ConclusionOur findings demonstrate a significant association between high cumCVAI and an increased incidence of GI cancers. Prolonged maintenance of CVAI within optimal levels may serve as a potential preventive strategy for GI cancers.